Minimizing postharvest food losses: a vital strategy to alleviate food insecurity and malnutrition in developing nations: a review - Ayesha Ashraf Khan; Yasmeen Siddiqui; Kadambot H. M. Siddique; Jack A. Bobo; Asgar Ali (Discover Food)
Abstract As global food production encounters escalating challenges, postharvest losses (PHLs) emerge as a critical yet often overlooked issue. Despite considerable progress in food production, PHLs remain a significant concern, accounting for an average of 14% of food production in 2021. Against the backdrop of 811 million people facing food insecurity and the triple burden of malnutrition, it becomes increasingly evident that reducing food losses offers a sustainable solution to enhancing global food and nutritional security, particularly in developing countries. This review aims to underscore the significance of PHLs, their impact on global food security, and the current PHL scenario in developing nations. Despite the abundance of innovative technologies developed by researchers, accessibility to these technologies remains limited for farmers in many countries. The ongoing struggle and dire circumstances surrounding proper food handling in developing nations necessitate immediate action. Research efforts must focus on assessing the regional applicability, costs, and economic returns of existing technologies for mitigating PHLs. In addition to capital investments, the long-term sustainability of reducing PHLs hinges on ensuring the effective use of these technologies through education and training. Graphical Abstract